The importance of the preliminary assessment of students’ knowledge in the process of teaching the discipline “The basis of genetics” - Palikyan, Spartak
The article describes and considers the possibility of applying the results of preliminary testing of student’s knowledge for increasing the effectiveness of teaching the courses within the frame of higher professional education, for which the school knowledge acts as basic. In this case the example of the course of "The Basics of Genetics" is discussed.
Keywords: Education